Disassembly sequence planning validated thru augmented reality for a speed reducer. Issue 1 (31st December 2022) - Frizziero, Leonardo; Donnici, Giampiero; Santi, Gian Maria; Leon-Cardenas, Christian; Ferretti, Patrich; Pascucci, Gaia; Liverani, Alfredo
Abstract: The lifecycle of a product is getting shorter in today's market realities. Latest developments in the industry are heading towards achieving products that are easy to recycle, by developing further technological advances in raw materials ought to include input from End of Life (EOL) products so a reduction of natural harm could be achieved, hence reducing the overall production environmental footprint. Therefore, the approach taken as a design for environment, a key request nowadays in order to develop products that would ease the reverse manufacturing process leading to a more efficient element recycling for later use as spare parts or remanufacturing. The methodology proposed compares three probable disassembly sequences following a comparison of literature-found procedures between genetic algorithms and as a "state space search" problem, followed by a hybrid approach developed by the authors. Time and evaluation of these procedures reached to the best performing sequence. A subsequent augmented reality disassembly simulation was performed with the top-scored operation sequence with which the user is better able to familiarize himself with the assembly than a traditional paper manual, therefore enlightening the feasibility of the top performing sequence in the real world.